Membrane Protein Complexes: Structure and Function (Subcellular Biochemistry,, 2018)
This edited book contains a compilation of 14 advanced academic chapters dealing with the structure and function of membrane protein complexes. This rapidly advancing important field of study closely parallels those on soluble protein complexes, and viral protein and nucleoprotein complexes. Diverse topics are included in this book, ranging from membrane-bound enzymes to ion channels, proton pumps and photosystems. Data from X-ray crystallography, cryo-electron microscopy and other biophysical and biochemical techniques are presented throughout the book. There is extensive use of colour figures of protein structures. Throughout the book structure and function are closely correlated. The two editors, Egbert Boekema and J. Robin Harris, have worked on aspects of membrane and soluble proteins throughout their scientific careers and also have much publishing experience. The Subcellular Biochemistry series has expanded considerably in recent years, including several related volumes. The theme of protein complexes will be continued within several future volumes, thereby creating encyclopaedic coverage. The chapter topics within this book are particularly relevant to those involved in the biological and biomedical sciences. It is aimed at the advanced undergraduates, postgraduates and established researchers within this broad field. It is hoped that the book will be of interest and use to those involved with the study of cellular membranes and their associated proteins.